Effects of Phaseic Acid and Dihydrophaseic Acid on Stomata and the Photosynthetic Apparatus - Sharkey, Thomas D. (1980)
Plant extracts containing phaseic acid (PA), as well as solutions of purified PA and dihydrophaseic acid (DPA) were applied to leaves, isolated mesophyll cells, and isolated epidermal strips. In Commelina communis, stomatal closure began 4 minutes after the addition of either 20 micromolar (±)-abscisic acid or 10 micromolar PA. Stomata closed less rapidly after treatment with 10 micromolar PA than after treatment with 10 micromolar (±)-abscisic acid in Amaranthus powelli, Hordeum vulgare, Xanthium strumarium, and Zea mays and did not respond at all to PA in Vicia faba. DPA (10 micromolar) did not cause stomatal closure in any species. Plant extracts containing PA reduced photosynthesis, as reported by Kriedemann et al. (Aust J Plant Physiol 2: 553-567, 1975). Subsequent experiments with PA purified by crystallization and with residues of solvents employed in the extraction of PA proved that it was not PA that impaired photosynthetic O(2) evolution or CO(2) uptake but unidentified contaminants of the allegedly pure solvents.